2017
DOI: 10.4103/0366-6999.217089
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Gd-RGD Imaging Study of Hepatocellular Carcinoma with High and Low Metastatic Potential before and after Human Bone Marrow-derived Mesenchymal Stem Cell Intervention

Abstract: Background:Biotherapy based on human bone marrow-derived mesenchymal stem cells (BMSCs) is currently the focus of research, especially in the field of autologous stem cell transplantation. A novel type of metastasis-associated magnetic resonance (MR) molecular imaging probe was constructed, and the changes in metastasis and proliferation of hepatocellular carcinoma (HCC) before and after BMSC intervention were observed through MR imaging (MRI).Methods:Metastasis-associated MR molecular imaging probe, integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…A SUVmean ratio of ≥ 1.551, a SUVmax ratio of ≥ 1.629 and a SUVmean ratio combined with SUVmax ratio of ≥ 0.759 identi ed as the best cut-off value to determine LoVo tumor from LS174T tumor. Our results were in line with the available published reference, as recently research showed that the contrast-to-noise (CNR) indexes of the Gd-RGD tracers in MRI was suitable for differentiating hepatocellular carcinoma (HCC) tissues with high metastatic potential from those with low metastatic potential [28]. However, the present study also had its limitation due to only two kinds of CRC cell lines with different metastatic potentials included in the comparative study.…”
Section: Discussionsupporting
confidence: 89%
“…A SUVmean ratio of ≥ 1.551, a SUVmax ratio of ≥ 1.629 and a SUVmean ratio combined with SUVmax ratio of ≥ 0.759 identi ed as the best cut-off value to determine LoVo tumor from LS174T tumor. Our results were in line with the available published reference, as recently research showed that the contrast-to-noise (CNR) indexes of the Gd-RGD tracers in MRI was suitable for differentiating hepatocellular carcinoma (HCC) tissues with high metastatic potential from those with low metastatic potential [28]. However, the present study also had its limitation due to only two kinds of CRC cell lines with different metastatic potentials included in the comparative study.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the decrease in metastatic potential following gene silencing in MHCC97-H was not associated with integrin α v β 3 expression, but was related to the decrease in OPN and TGFβ 1 expression. At lower levels, OPN and TGFβ 1 do not bind to integrin α v β 3 (39). Therefore, it is possible that low OPN and TGFβ 1 expression in MHCC97-H may reduce metastasis by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%